Implementasi Kerangka Integratif Kewirausahaan dalam Pendidikan Islam Studi Kasus SDI Al-Azhar 38 Bantul - Family Lativa, Lativa; Subiyantoro; Aziz Saputra, Muhamad Nur (Indonesian Journal of Action Research, 2025)
Purpose – This study aims to analyze the implementation of an integrative entrepreneurship framework in Islamic education at SDI Al-Azhar 38 Bantul. The study focuses on how entrepreneurial values are integrated into Islamic education, how school programs support the development of students’ entrepreneurial skills, and how Islamic values such as honesty, trustworthiness, discipline, responsibility, creativity, and independence are internalized through learning activities and school-based entrepreneurship programs. Design/methods – This study employed a qualitative approach with a case study design. Data were collected through interviews with Islamic education teachers, observations of learning and entrepreneurship activities, and documentation of curriculum, school programs, entrepreneurship modules, and evaluation documents. The data were analyzed through data reduction, data display, and conclusion drawing. To ensure the validity of the findings, the study used source and method triangulation by comparing interview, observation, and documentation data. Findings – The findings show that SDI Al-Azhar 38 Bantul implements an integrative entrepreneurship framework by connecting entrepreneurial concepts with Islamic education materials, classroom learning, extracurricular programs, project-based activities, Market Day, Student Led Conference, and the use of the Entrepreneur Lab. The integration is not limited to theoretical instruction but is practiced through students’ direct involvement in simple business projects, product creation, selling activities, and financial literacy exercises. Islamic values are embedded through daily habits and entrepreneurial practices, including honesty in transactions, discipline in worship and learning, responsibility in group projects, and creativity in producing marketable products. The supporting factors include competent teachers, school facilities, an integrative curriculum, parental involvement, foundation support, and regular teacher development activities. The challenges include the adaptation of new teachers, limited selling time, insufficient product display space, and students’ lack of confidence in offering products. Overall, the implementation contributes to the development of students’ soft skills, hard skills, independence, creativity, communication skills, teamwork, and Islamic entrepreneurial character.